The impedance of hydrogen oxidation reaction in a proton exchange membrane fuel cell in the presence of carbon monoxide in hydrogen stream. (1st December 2020) - Darowicki, K.; Gawel, L.; Mielniczek, M.; Zielinski, A.; Janicka, E.; Hunger, J.; Jorissen, L.
Highlights: Carbon monoxide pollution of hydrogen stream. On-line impedance changes of anode exposed to different concentrations of carbon monoxide. Evaluation of carbon monoxide surface coverage of anodic catalyst. Coherence between AC and DC measurements by self- validation methodology. Abstract: Evaluation of performance of a proton exchange membrane fuel cell, which is affected by carbon monoxide that pollutes the hydrogen stream, was presented. This influence was studied for carbon monoxide concentration of 125–325 ppb, which are close to values specified in ISO 14687:2019 standard. Performed studies provided crucial information for further development of fuel cell as an energy source for automotive application. Impedance with the use of Dynamic Electrochemical Impedance Spectroscopy profile measurements were completed for chosen carbon monoxide concentration under a constant current load and anode impedance variations were determined as a function of the time exposed to carbon monoxide. A method to determine the impedance of hydrogen oxidation was proposed. It was determined how the carbon monoxide surface coverage of anodic catalyst varies as a function of time. The capacitance of the double electrical layer and the charge transfer resistance of anodic reaction are discussed to evaluate them with respect to exposure time and surface coverage. It has been shown that proposed methodology can be used as a universal tool for testing fuel cells for both research and industrial applications, with the overall aim of optimization, monitoring, and diagnostics of the fuel cell.